OUTCOMES OF MICROSURGICAL TREATMENT OF CHIARI TYPE I MALFORMATION USING A DIFFERENTIATED INTRAOPERATIVE STRATEGY FOR DETERMINING THE EXTENT OF INTERVENTION (Modern American Journal of Medical and Health Sciences, 2025)
Despite the presence of numerous publications and analytical reviews in the international literature, a universally accepted algorithm for the surgical treatment of Chiari malformation type I (CM-I) does not currently exist. In the domestic literature, the number of publications devoted to the surgical management of CM-I remains limited, which, in our opinion, highlights the relevance of this study.